The Effectiveness of Implementing Family-Centered Rounds in the PICU on Parental Satisfaction - Arvina Novianti; Sita Febriani; Hermin Mardiana; Rismala Dewi; Dina Nurpita Suprawoto (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2023)
Family-Centered Care (FCC) is needed in nursing care for children with critical illnesses in the PICU, but the implementation of FCC has yet to be effective. This is due to family visit restrictions, direct care involvement, and decision-making. Family- Centered Rounds (FCR) are a multidisciplinary professional approach to decision-making by facilitating family involvement in medical decision-making. This study aims to analyze the effectiveness of implementing FCR in the PICU on patients' parents' satisfaction. This study used a quantitative experimental design in which Randomized Controlled Trial (RCT) design with a post-test-only control group was used. Sixty-four parents of patients in the PICU unit at RSCM were recruited by consecutive sampling and randomly assigned to two treatments (room standard intervention for the control group and FCR for the intervention group). Treatment in both groups was carried out for two days then the satisfaction level of parent respondents was measured using the Pediatric Family Satisfaction in intensive care Unit 24 (pFS-ICU 24). Bivariate analysis used an independent t-test to analyze differences in family satisfaction scores in both groups. Statistically, there was a significant difference in the mean score of patient family satisfaction between groups with FCR and no FCR with p=0.001 (p<0.05). It was concluded that FCR was effectively carried out, which impacted increasing the satisfaction of the patient's parents. FCR is very effectively implemented in the PICU unit as a development of the application of the FCC concept, which can benefit the patient's family.